Experimental analysis of effective energy dosage in hot air weeding. (December 2022) - Morselli, Nicolò; Ottani, Filippo; Puglia, Marco; Pedrazzi, Simone; Tartarini, Paolo; Allesina, Giulio
Abstract: The Sustainable Development Goals constitute a series of shared targets aimed at achieving a better and more sustainable future for all. To date, urban and rural environments need to have several management practices reviewed in order to meet the above-mentioned goals. In the agricultural sector, weeds are the principal cause of crop yield reduction and an effort is required to abandon chemical herbicides, increasingly disincentivized by the European Union and agricultural regulations. This work applies research to innovative thermal methods for weed control in specialized crop (e.g. vineyards or orchards), investigating the energy dosage needed when hot-air weeding technology is used. Through a table-top experimental setup, a series of empirical equations are defined to correlate the effectiveness and working area of the hot air technology to the main governing parameters of the thermal weeding: temperature and residence time of the heat source (air). The equations highlight different ways in which it is possible to energetically optimize this technology: primary energy savings of 2.8 times can be obtained if the weeding effectiveness is reduced from 90 to 80%, while, maintaining the same effectiveness, it is possible to increase the residence time and to work at low air temperatures (150–200 °C) avoiding the risk of fire that often hinder the spread of thermal weeding practices. Graphical abstract: